Pre-Service English Language Teachers’ Digital Competence in Developing Interactive Learning Media - Mohamad Ikbal Hamzah; Novriyanto Napu; Helena Badu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The increasing demand for technology-enhanced instruction in English Language Teaching (ELT) highlights the importance of developing strong digital competence among pre-service teachers, especially in designing interactive learning media. This study aimed to examine how pre-service English language teachers perceived their digital competence in developing interactive learning media during the Field Experience Program (PPL). Consists of 10 participants from the ELESP 2022 cohort at Universitas Negeri Gorontalo. Guided by the DigCompEdu framework, the research focused on three domains closely related to media production and pedagogical application: Digital Resources, Teaching and Learning, and Empowering Learners. Using a descriptive qualitative design, data were collected through semi-structured interviews and were analyzed thematically. The findings show that participants possessed fundamental operational skills in using tools such as Canva, PowerPoint, Wordwall, and Baamboozle to create multimodal and gamified activities that enhanced student engagement and comprehension. However, they reported limited expertise in advanced media design, contextual adaptation, and facilitating collaborative digital learning. Challenges were linked to insufficient practical training during coursework, unstable internet access, limited school devices, and dependence on free templates. Despite these constraints, participants expressed strong motivation to improve their digital teaching competence. The study highlights the need for teacher education programs to reinforce experiential digital pedagogy through hands-on workshops and project-based media development to better prepare pre-service teachers for designing inclusive and effective technology-integrated learning environments.